Burnout syndrome and job performance among health science teachers - Parra-Gálvez, Katherine Fiorella (2023)
Objective: This article aims to show the impact of Burnout Syndrome on the work performance of health sciences teachers. Materials and Methods: For this purpose, a search of original articles, review articles, theses, and systematic reviews published from 2017 to 2022 was conducted in the databases: Pubmed/MEDLINE, Scopus, SciELO, and Google Scholar. Results: According to the results obtained, it is concluded that medical and dental teachers do have a high tendency to suffer burnout, which affects their final performance with the student, having negative consequences in the teaching-learning process. Conclusion: Burnout syndrome is associated with professionals who perform a direct service to other people, this being the case of teachers. The professors of health sciences faculties represent a population at high risk for the development of chronic occupational stress, because, in addition to the constant interaction with students, the workload inside and outside the institution, the social responsibility involved in training professionals who develop the necessary skills to care for the health of others; they also perform care work that can increase the levels of burnout in them, directly affecting their work performance.